Food: God’s Gift to All People. Case Study from Croatia - Begić, Martina Ana (Studia Ecologiae et Bioethicae, 2024)
In the light of the biblical message, food is God’s gift to all people. Church’s documents emphasize that food is a natural human need, and every human has a natural right to food. This, however, presents new challenges to humanity today, because market-oriented agriculture often prevails, which does not focus so much on the quality and availability of food for all people, especially the poor, but puts profit at the center. The first part of paper attempts to concisely present the attitude of the Holy Scriptures towards food, which contribute to today’s reflection on solving the problem of production and availability of healthy food. The second part presents church’s guidelines, aimed to overcome today’s injustices in the world and provide everyone with access to food, and highlights the importance of producing healthy food for the protection of health. The third part of the paper deals with certain decrees on food production and control and the promotion of ecological production in the Republic of Croatia. Nevertheless, adopting the legislation of the European Union and accepting its guidelines on the development of agriculture has brought a certain shift in recent years. This legislative framework will contribute to the strengthening of the Croatian rural community, the encouragement of small family farms, and the increase of food production, especially healthy, ecologically grown food.